Model Kepemimpinan Berbasis Weton: Mengintegrasikan Kebijaksanaan Budaya Jawa ke dalam Manajemen Organisasi Modern - Choirul Anam; Muhammad Saiful Rijal; Iva Khoiril Mala (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study developed the Weton-Based Leadership Model as a leadership framework that integrates Javanese cultural values from the weton system with modern leadership theories, such as transformational, servant, charismatic, and situational leadership. Using a postmodern paradigm with an exploratory qualitative approach, this study utilizes pattern matching and explanation building methods through in-depth interviews with cultural experts and human resource management practitioners, as well as analysis of Javanese cultural documents. The results of the study identify five key components in the model, namely self-awareness, value alignment, situational adaptability, team harmony, and risk governance. These five components interact with each other to form contextual leadership that is in harmony with personal identity, organizational culture, and environmental demands. The practical implications of this study include the use of weton as a reflective instrument in recruitment, personalized leadership development, and the strengthening of an inclusive organizational culture. Further research is recommended to test this model in various industrial contexts through quantitative methods and longitudinal approaches.